EXPLORING PROSODY OF STUTTERING DISORDER EXPRESSED ON MATICE AHNJAMINE VLOG - Fika Nadiyah Umi Salwa; Rohmani Nur Indah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
This study aims to identify the type of stuttering and analyze intonation that appears on Matice Ahnjamine in her YouTube vlog. Matice’s videos contain her stuttering life. The stuttering disorder as the difficulty in speaking can be seen from its type and the intonation pattern used when making statement. The research data are in the form of words, phrases, and sentences from the selected videos. The data analysis employs Zebrowski's theory (2003) on the type of stuttering, also a combination of Gimson (1975) and Wells (2006) theories in analyzing intonation in Matice's declarative sentences. The findings show four types of stuttering made by Matice, namely repetition, silent pause, prolonged vowel, and interjection. In addition, the intonation used in her speech shows that in the final words and stuttering words have different intonations because when stuttering words appear sometimes the intonation is not clear. Based on the findings, the dominant type of stuttering type appears is repetition and the intonation which often used at the end of the final word is falling intonation.